Faith-Based Worldviews as a Challenge to the Believing Game - Patricia Bizzell (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Elbow's "Believing Game" may help to make room in the academy for religious frames of mind, which encompass particularly dense networks of ideas and emotions.